Refleksi Standar Akuntansi Pemerintah dalam Manifestasi Good Governance - Nufaisa; Ade Irma Suryani Lating; Mohammad Dliyaul Muflihin (Akuntansi : Jurnal Akuntansi Integratif, 2022)
This study aims to understand the implementation of government accounting standards in realizing good governance in Gunung Anyar District, Surabaya in terms of human resource competence. The research material consists of the characteristics of accrual-based financial statements, as well as the principles of good governance. This research is a qualitative research. Data collection techniques were carried out by observation, interviews and documentation studies. There were three informants selected, namely the sub-district head, the general and staffing section, and the finance section. An interpretive approach is used to describe a deep understanding of the process of government accounting standards in terms of the competence of its human resources to realize good governance in Gunung Anyar District, Surabaya. The results of this study are that in general accrual basis government accounting standards have been carried out well although in some cases further improvements and improvements are needed. The educational background of the human resources who carry out the accrual basis process, namely the KA Sub Division of Finance, is not appropriate, and it can be said that transparency is due to the fact that financial performance can be accessed via the internet. So that the public knows clearly about the financial statements.